1349. How Anchored is the Chancre? A Chart Review of Syphilis Treatment by a Safety Net Emergency Department in Atlanta, GA. (4th December 2021) - Gruen, Judah; Sharp, Joseph; Sweitzer, Stephanie
Abstract: Background: Since reaching its nadir in 2000, syphilis has re-emerged as a public health threat in the U.S. The incidence of syphilis is disproportionately high in Atlanta, the epicenter of the HIV epidemic in the U.S. South. Given that syphilis infection is a strong predictor of HIV infection, identifying patients with syphilis is an important and underutilized method for connecting patients to HIV prevention and care services. Emergency departments (EDs) act as a critical access point to care in safety net health systems. We describe the recognition and empiric treatment of syphilis in the ED of Grady Healthcare System, a safety net hospital serving Atlanta. Methods: We performed a retrospective chart review on all reactive rapid plasma reagin (RPR) tests collected from patients 18 years and older at the Grady ED from 5/1/20 to 10/31/20. We abstracted reported reason for testing, diagnosis, treatment administered, and location of treatment from the electronic health record. Results: From 5/1/20 to 10/31/20, 148 patients with reactive RPR tests were identified. Reasons for testing were broad and included the evaluation of neurologic symptoms (47), genital/anal lesions (31), and a history of syphilis (18) (Table 1). 74 patients had presumed active syphilis (50%), 34 had previously treated syphilis (23%), 12 had false positives (8%), and 28 had an unclear diagnosis (19%) (Table 2). Of those with presumed primary syphilis who were discharged from the ED, 53% (8/15) received empiric treatment in the ED; 59% (10/17) of those with secondary syphilis received empiric treatment prior to discharge. Of the patients discharged from the ED, clinical follow up was indicated for 52% (31/59) given lack of empiric treatment or of confirmed prior treatment. Contact was attempted for 39% (12/31), but only 29% (9/31) were ultimately treated at Grady. Table 1: Abstracted Reasons for Testing for Syphilis in the ED For ED patients from 5/1/20-10/31/20 who had reactive RPRs, reasons for syphilis testing were taken from the chief complaint, history, or medical decision making documentation of ED providers, admitting providers, or consultants. Table 2: Syphilis Diagnoses of ED patients with reactive RPRs ED patients with a positive RPR from 5/1/20-10/31/20 were chart reviewed to determine their diagnosis. Previous RPR, treponemal antibodies, CSF results, media images, progress notes, and descriptions by medical staff were reviewed to attempt to retroactively determine the most likely syphilis diagnosis. Conclusion: Reactive RPRs were common in this acute care setting and most represented active syphilis infection. Empiric treatment was most likely to be provided for patients with clear syphilis syndromes. However, a majority of patients who were discharged without empiric treatment did not receive follow up. Institutional protocols for following up reactive tests after discharge represent an opportunity to connect patients with syphilis treatment and HIV prevention services. Disclosures: All Authors : No reported disclosures